Family, Peer, and School Influences on Children's Developing Health Lifestyles - Mollborn, Stefanie (J Health Soc Behav, 2018)
Health lifestyles are important for health and social identity, yet little is known about their development in early life. We use data from the Early Childhood Longitudinal Study, Kindergarten Class of 1998-99 (ECLS-K; N=8786) to track children's health lifestyles and assess a theoretical model of health lifestyle development. Latent class analyses identify health lifestyles at four time points from first to eighth grade, and multivariate models investigate their interrelationships and social contextual influences. Health lifestyles are multidimensional and dynamic, and children demonstrate distinct combinations of risks and protections. Family factors such as resources and parenting shape earlier health lifestyles, which influence later lifestyles. Results show that development and contexts drive changes in health lifestyles, as family factors decrease in influence with age while some school and peer influences appear to emerge. Policymakers and researchers interested in shaping health behaviors should consider the multidimensional and dynamic nature of health lifestyles.